Importance of early endoscopic and clinical evaluation of children with caustics ingestion - Enory Almanza-Miranda; Gerardo Blanco-Rodriguez; Jaime Penchyna-Grub; Gustavo Teyssier-Morales; Rubén Peña-Vélez (Permanyer, 2021)
Background: Accidental ingestion of caustics in pediatrics continues to be a frequent problem that can lead to severe injuries and permanent sequelae that require esophageal rehabilitation programs. This study aimed to describe the medical care experience of children who ingested caustic substances in a tertiary hospital in Mexico City. Methods: We conducted a descriptive and analytical study. We described age, sex, type of caustics, clinical and endoscopic findings, and the radiological evolution of 284 patients who arrived during the acute phase. Results: The records of 336 children with a history of caustic ingestion were reviewed. The median age was 1.7 years, and the predominant sex was male. Caustic soda was the most accidentally ingested substance. We found an association between the severity of the esophageal injury with the presence of more than four symptoms at diagnosis (χ², p < 0.001) and with the finding of oral lesions, sialorrhea, and vomiting (χ², p < 0.05). Forty percent (n = 114) showed normal gastrointestinal endoscopy. Conclusions: In children with caustic ingestion, upper gastrointestinal endoscopy should be performed within 72 hours to evaluate the extent of the lesions. In this study, we found that more than four symptoms at admission, and oral lesions, sialorrhea, and vomiting are associated with the severity of the esophageal injury.